Study of some Impact Of Enterococcus faecium As Probiotic On Chick 1- Body Weight And Pathological Changes In Air Sacs And Intestine: Emad J.khamas and Amjad H.Elaywe - khamas, Emad J. (The Iraqi Journal of Veterinary Medicine, 2007)
To investigate the impact of Enteococcus faecium as probiotic in layer chicks,this bacteria was given in feed at a dose rate of 1.5 gm per kg feed, each kg offeed contained 5×1011 cfu along the period of the study (57 days). 150 one dayold males were divided into five groups, 30 males each. The 1st group was giventhe probiotic only in the feed, the 2nd group was given the probiotic and exposedto high temperature and bad ventilation as a stress, and the third group wasgiven the probiotic with chlortetracycline in feed while the fourth group wasgiven the probiotic and then infected with E. coli on 21 day of age and the fifthgroup was given feed with out probiotic as the control group. The resultsshowed that there was increase in body weight especially in the last weeks of theexperiment. Turbidity of the air sacs was mild in the four group compared withcontrol. Intestinal villi became elongated due to using of probiotic and there wasless sloughing compared with control, and those groups showed resistancetoward E. coli infection.